PERSEPSI ATAS PENGGUNAAN MEDIA POWER POINT DAN MOTIVASI TERHADAP PRESTASI BELAJAR SOSIOLOGI - Yulianto Yulianto; Sri Hapsari (Herodotus: Jurnal Pendidikan IPS, 2019)
The purpose is to determine how much influence the perception of the use of power point media and motivation on sociology learning achievement. The research method used is a survey method with correlational analyst,  with the help of a questionnaire, and it can be concluded that: (1) There is a significant influence on the perception of the use of power point media and motivation together on the sociology learning achievement . This is evidenced by the acquisition of Sig = 0,000 <0.05 and Fcount = 19,695. (2) There is a significant influence on the perception of the use of power point media on the sociology learning achievement. This is evidenced by the acquisition of Sig = 0,000 <0.05 and tcount = 2.325. (3) There is a significant influence of motivation on sociology learning achievement. This is evidenced by the acquisition of Sig = 0,000 <0.05 and tcount = 3.828.